PENGARUH MODEL PEMBELAJARAN KOOPERATIF TGT (TEAM GAME TOURNAMENT) TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI KEMAMPUAN NUMERIK SISWA KELAS V SD - Laili Alfi Rahmatin (JURNAL ILMIAH GLOBAL EDUCATION, 2020)
This research aims to describe the effect of the TGT (Team Game Tournament) type learning model to improve students' learning outcomes in terms of numerical abilities. The population in this research were fifth grade elementary school students in the Setuta village, District Janapria, Central Lombok Regency, in the academic year 2019/2020, with a sample of 68 students'. The sample of this research was using random sampling technique. Data on Numerical ability and mathematics learning outcomes were collected through tests and analyzed using two-way ANOVA analysis followed by Tukey's test. The results of this research indicate that the TGT cooperative learning model has a significantly better impact on mathematics learning outcomes compared to conventional ones. Thus it can be concluded that the used of TGT cooperative learning can improve student learning outcomes, both cognitive and affective. In addition, TGT cooperative learning was very pleased by students, it was proven that the students gave a positive response with the happy attitude scale category.